Enzyme Inhibitory, Physicochemical, and Phytochemical Properties and Botanical Sources of Honey, Bee Pollen, Bee Bread, and Propolis Obtained from the Same Apiary - Yusuf Can Gercek; Eda Dagsuyu; Fatma Nur Basturk; Seran Kırkıncı; Nazlıcan Yıldırım; Gamze Kıskanç; Bahar Özmener; Yigit Sabri Unlu; Seda Nur Kalkan; Kadir Boztaş; Gül Cevahir Oz; Refiye Yanardağ; et al. (Antioxidants)
Bee products are an important source of nutrients and bioactive phytochemicals. This study aimed to determine the chemical composition (proximate composition, general phytochemical composition, sugar, and phenolic profiles) of four different products (honey, bee pollen, bee bread, and propolis), obtained from the same apiary, as well as to assess their biological activity through antioxidant and enzyme inhibition assays (α-amylase, α-glucosidase, lipase, AchE, neuraminidase, angiotensin-converting enzyme, urease, trypsin, tyrosinase, carbonic anhydrase, thioredoxin reductase, adenosine deaminase). Clear differences were observed among the samples in terms of both chemical composition and biological activity. The analysis revealed that bee pollen exhibited the highest carbohydrate content (87.9%), while propolis was identified as the richest source of phenolic compounds (14,858.9 mg/kg) among the analyzed samples. Propolis exhibited the highest biological activity in all applied antioxidant assays (CUPRAC, DPPH•, and ABTS•+) and in most enzyme inhibition assays. Notably, the α-glucosidase inhibition activity of propolis was comparable to that of the reference standard. In addition, honey exhibited remarkable trypsin inhibition, also comparable to the applied standard. These findings highlight the diverse bioactivities of hive products, which could play a key role in promoting health and preventing diseases.